Poetyka etiudy Klary Kochańskiej Lokatorki - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The article provides a comparative analysis of the style and composition of Klara Kochańska’s student short feature film Lodgers. (produced by the Polish Nation Filmschool in Łódź in 2015) as an example of film narrative practices typical of the academic exercises of students today.